The impact of vegetarianism and veganism on health and longevity - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Results of a study on the effects of vegetarian diet on premature mortality for various reasons are recently published in Critical Reviews in Food Science and Nutrition. This is a review of these results as other related works.